Evaluation of Provision of Compensation Based on Salary Mapping (Adhered and Overlapping) In Continent Shop SMEs - Farikul Fathi Ardian; Refindi Rizky Ramadhoni; Yabes Mulya; Rosyifa Salsabila Auliya Sahili; Galan Subiansyah; Ryan Ridhal Adhim (International Journal of Social Service and Research, 2022)
In the current pandemic period, every company is encouraged to increase high productivity in order to be able to compete with its competitors. One of the factors that affect the effectiveness and efficiency of a company is the performance of its employees. To motivate the increase in the performance of employees of a company, namely by providing the best possible compensation. Compensation within a company is an important element because the determination of the size of the compensation given indirectly has an impact on the company's performance. UKM Toko Continent is one of the grocery grocery stores in Lenek, East Lombok. This study aims to compare the compensation received by employees at Continental Stores. For data collection, it is done by distributing online questionnaires through google form media to employees. This study uses quantitative and qualitative data that we obtained from distributing online questionnaires in order to describe in detail the compensation system applied to UKM Toko Continent. In this UKM, the compensation system has not yet been implemented, so it is necessary to evaluate the position of the amount of compensation received by using the adhered and overlapping salary mapping methods. This method was chosen because it is an analytical and quantitative method, where positions are assessed according to a number of factors in detail, and the value of each position is expressed in numbers. With this method, a fair payroll system is in accordance with the UMK/UMP in SME locations. After evaluating the position using the salary mapping method, there was an increase in salary in accordance with the work done